The book of virtues : a treasury of great moral stories (Melbourne : Bookman Press, 1993)
Well-known works including fables, folklore, fiction, drama, and more, by such authors as Aesop, Dickens, Tolstoy, Shakespeare, and Baldwin, are presented to teach virtues, including compassion, courage, honesty, friendship, and faith.
Includes index.
Keywords: Literature